Project Report on Analysis and Design of Multistoreyed Building - SANJAY KUMAR SINGH, SHAKIR AHSAN MALLICK, MOHAMMAD SABIR, SARFARAJ ALAM and SUNIL KUMAR SINGH (1992)
INTERNAL GUIDE:JAYAPALAN S, MVJCE
Keywords: Analysis and Design of Multistoreyed Building